Exploring Impulsive Budgeting Behavior in Local Governments: A Phenomenological Perspective - Adam, Mukhtar A.; Nurdin, Nurdin; Zainuddin, Zainuddin (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2025)
The phenomenon of unproductive and impulsive government spending, as well as the misalignment between the needs of the government and those of the public, is the central concern of this study. It seeks to uncover impulsive behavior among budget management officials in regional governments. The researcher observes that budget managers tend to spend in accordance with the DPA-SKPD merely to meet budget absorption targets, without considering the output, outcome, or benefits of such expenditures. Meanwhile, from the perspective of the Regional General Treasurer (Bendahara Umum Daerah), payments are often made solely based on realization requests, without thorough planning for each financial transaction. These decisions are primarily influenced by pressure and situational factors rather than being based on well-considered planning in terms of budgeting, cash management, or the actual benefits of the resulting outputs. This study aims to analyze the situational factors influencing impulsive spending behavior by activity managers in relation to budget realization decisions. The research adopts a qualitative approach using a phenomenological study design. Key informants were selected through purposive sampling, consisting of five research subjects: the Head of SKPD (Regional Work Unit), activity planners, activity implementers, financial managers, and the Inspectorate. The findings reveal that all key informants engaged in spending based on the DPA-SKPD, influenced by external pressure, fund availability, and procedural compliance, without adequately considering the actual needs and benefits of the goods and services procured. A comprehensive approach involving participatory planning, control, supervision, and management of government goods and services is essential to ensure that every public expenditure effectively contributes to regional development. This study offers theoretical contributions to the development of behavioral theories in regional public financial management and provides practical implications for the formulation of performance-based budgeting that incorporates budgetary considerations, actual needs, and the utility of goods and services for both the government and the public.